Effective fundraising : the trustees role and beyond - McFarlan, F. Warren (Franklin Warren) (John Wiley & Sons, Inc., 2021)
"This book is about development. In Joining a Non-Profit Board: What You Need to Know we laid out three roles for the board of trustees: 1. The definition and approval of the organization's mission and the strategy to achieve it. 2. The selection, coaching and evaluation of the CEO. 3. The securing of the necessary financial resources for the organization. This book has focused on the third of these roles; the one that social enterprise CEOs repeatedly say consumes 50% of their time. Without funds, mission cannot be fulfilled. Development is the lifeblood of most social enterprises, be they large or small. It is the unique and special responsibility of its trustees and supporters to help secure resources for the organization. These resources are often critical to the organization's success if not survival. There are many ways that individual trustees, given their resources and skill sets, can go about this task. Attracting and harnessing the energies of the right people is key to the long-term success of development."--